Temperature dependent Young's modulus and quality factor of CMOS-MEMS resonator: Modelling and experimental approach. (February 2016) - Jan, Mohammad Tariq; Ahmad, Farooq; Hamid, Nor Hisham B.; Md Khir, Mohd Haris B.; Ashraf, Khalid; Shoaib, Muhammad
Abstract: CMOS-MEMS resonators are the key parts of modern integrated systems. Most of these resonators are fabricated through CMOS composite layers that are sensitive to temperature. In this article, the effects of temperature on the collective Young's moduli and quality factor of CMOS composite layers based MEMS resonator are theoretically modelled and experimentally validated. A custom made environmental chamber is used to control the environmental effects and an external vibration shaker is used to actuate the fabricated CMOS-MEMS resonator at its resonance frequency in the presence of a permanent magnet. Variations with increasing temperature in the collective Young's moduli of the CMOS composite layers are determined through the measurement of change in resonance frequency of the resonator and found to be linear. A nonlinear behaviour of the quality factor is noticed in the temperature range of 25 °C to 80 °C, the quality factor is found to be increasing whereas from 60  ∘  C to 80  ∘  C, the quality factor is decreasing. Highlights: The effects of temperature on the collective Young's moduli and quality factor of CMOS composite layers based MEMS resonator are theoretically modelled and experimentally validated. A custom made environmental chamber is used to control the environmental effects and an external vibration shaker is used to actuate the fabricated CMOS-MEMS resonator at its resonance frequency in the presence of a permanent magnet Variations with increasing temperature in the collective Young's moduli of the CMOS composite layers are determined through the measurement of change in resonance frequency of the resonator and found to be linear. A nonlinear behaviour of the quality factor is noticed in the temperature range of 25°C to 80°C